Chlorogenic acid induces apoptosis, inhibits metastasis and improves antitumor immunity in breast cancer via the NF-κB signaling pathway - Zeng, Anqi (Oncol Rep, 2021)
Breast cancer which is the most common type of diagnosed cancer among women worldwide possesses metastatic potential, multi-drug resistance, and high mortality. The NF-κB signaling pathway has been revealed to be abnormally activated in breast cancer cells and closely associated with high metastasis and poor prognosis. In the present study, it was reported that chlorogenic acid (CGA), a potent NF-κB inhibitor derived from coffee, exerted antitumor activity in breast cancer. MTT and colony formation assays were conducted and it was revealed that CGA inhibited viability and proliferation in breast cancer cells. Additionally, CGA significantly induced apoptosis and suppressed migration and invasion in breast cancer cells. Notably, immunofluorescence analysis confirmed that CGA could efficiently suppress nuclear transcription of NF-κB p65. In addition, results of western blotting demonstrated that CGA markedly impaired the NF-κB and EMT signaling pathways. The antitumor effect of CGA was evaluated in a subcutaneous tumor mouse model of 4T1 cells, and the results revealed that CGA markedly retarded tumor growth and prolonged the survival rate of tumor-bearing mice. Notably, CGA inhibited pulmonary metastasis of 4T1 cells by enhancing the proportion of CD4(+) and CD8(+) T cells in spleens of mice, which indicated an improvement of antitumor immunity. In conclusion, the present present study demonstrated that CGA improved antitumor immunity, exerting antitumor and anti-metastatic effects by impairing the NF-κB/EMT signaling pathway, suggesting that CGA may serve as a potential candidate for therapy of breast cancer.